Pengaruh IQ, Pengalaman, Perilaku & Motivasi terhadap Kinerja Pegawai Pemerintah Kabupaten Karimun - Roy Erisusanto; Bambang Satriawan; Muammar Khaddafi (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to determine the effect of intellectual intelligence, work experience, and work behavior on employee performance through work motivation of Government Employees with Technical Group Work Agreements in Karimun Regency Research methodology: Stratified Random Sampling: Used for primary sampling of 131 people from 193 Government Employees with Work Agreements in Karimun Regency. The sample was divided proportionally according to the proportions in various regional government agencies and organizations. Population: 193 Government employees with Technical Group Work Agreements. Sample: 131 employees selected as research samples. Data Collection: Using a questionnaire as a data collection tool. Data Analysis Technique: Using Partial Least Square (PLS) with SMARTPLS software for hypothesis testing and data analysis. Results: Performance is influenced by intellectual intelligence, work experience, work behavior, and work motivation by 90.9%. Work motivation is influenced by intellectual intelligence, work experience, and work behavior by 71.7%. Conclusion: The results of this study help the Karimun Regency Government manage employee performance more effectively. It was found that intellectual intelligence does not directly affect performance, so the government needs to focus more on employee behavior and experience. Limitations: This study is limited to Government Employees with Technical Group Work Agreements in the Regional Apparatus Organization of Karimun Regency. The variables studied include intellectual intelligence, work experience, and work behavior as independent variables, performance as a dependent variable, and work motivation as an intervening variable. Contribution: Work experience increases motivation, which in turn contributes to performance, allowing the government to maximize work experience through developing employee motivation.